Efisiensi Modal Kerja, Agresivitas Pendanaan Modal Kerja, Efisiensi Persediaan, dan Kinerja Operasi Perusahaan di Indonesia - Iqbal, Mohammad; Rakim, Aditya Achmad (AL-QARDH, 2022)
This study examines the relationship between working capital efficiency, aggressiveness of working capital funding, and inventory efficiency with the operating performance of companies in Indonesia. This study uses 132 annual financial report data from 2004 to 2016. The research model was tested with Seemingly Unrelated Regression (SUR) and estimated using Feasible Generalized Least Squares (FGLS). Based on the model test results, there is a correlation error term between the equation systems so that the use of SUR is correct. The results showed that the more efficient working capital the higher the operating performance of the company and the more aggressive working capital funding the higher the operating performance of the company. This research does not support inventory efficiency where the company holds high inventory to realize demand in the market.